Study on breakthrough infection and effectiveness of COVID-19 vaccination among COVID-19 patients visited ayush triage center attached to McGann district teaching hospital, Sims-Shvaimoga, Karnataka, India: A longitudinal and retrospective study - Anupama Kavalibasappla,; Kanchana Nagendra ,; Prashanth Hebballi Lingaraj,; Raghavendraswamy Koppad,; Mandi, Mageppa; Darshitha Rajanna,; Shashi Kiran Guttinadu Mallikarjunappa, (Asian Journal of Medical Sciences, 2023)
Background: Novel coronavirus (COVID-19) first came to China in December 2019 and had become a public health emergency. There was a sudden rise of COVID-19 cases and its deaths. Aims and Objectives: This study intends to study the estimation of breakthrough infection among COVID-19 patients and to estimate the vaccination effectiveness among COVID-19 patients concerning the severity of the disease. Materials and Methods: This study was conducted in Mc Gann teaching hospital. The patients who were attending the Ayush Triage were included in the study. The sample size of 200 was estimated and the study was conducted for July 5–August 4, 2021, (1 month). A retrospective study design was planned and ethical board clearance was taken before starting the study. Patients were interviewed by telephone. The basic information such as contact number was collected by secondary data available in the triage center. Later details about Vaccination status and outcome of the disease were collected through telephonic interviews. Results: Among 200 COVID-19 patients, 28.5% of the patients had taken vaccination. The breakthrough (COVID-19 patients who had taken both doses) infection rate was 10.5% among the people who had been diagnosed with the COVID-19 infection. Most breakthrough infections were mild. The majority of the 163 (81.50%) did not know the source of infection. The majority of the patients 143 (71.50%) were not vaccinated. After the COVID-19 infection, only around 12 (6%) patients were not recovered completely, that is, they had a history of death or hospitalization, and the remaining 188 (94%) patients were completely recovered. Conclusion: Overall, one in every tenth individual after complete vaccination against COVID-19 infection had contracted the infection. Most of the breakthrough infections were mild and many of the subjects did not know the source of the infection.